2016
DOI: 10.1016/j.yjmcc.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline attenuates cardiac dysfunction in tumor-burdened mice

Abstract: Cardiovascular dysfunction as a result of tumor burden is becoming a recognized complication; however, the mechanisms remain unknown. A murine model of cancer cachexia has shown marked increases of matrix metalloproteinases (MMPs), known mediators of cardiac remodeling, in the left ventricle. The extent to which MMPs were involved in remodeling remained obscured. To this end a common antibiotic, minocycline, with MMP inhibitory properties was used to elucidate MMP involvement in tumor induced cardiovascular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In agreement with previous findings, we found depressed myocardial function in the hearts of tumor-bearing mice that reached significance at 19 days postinjection (7,41). This is most likely due to the LV wall being compromised, as evidenced by the reduction in PWTs.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous findings, we found depressed myocardial function in the hearts of tumor-bearing mice that reached significance at 19 days postinjection (7,41). This is most likely due to the LV wall being compromised, as evidenced by the reduction in PWTs.…”
Section: Discussionsupporting
confidence: 92%
“…As tumor effects and cachexia effects on the heart are occurring simultaneously, it is difficult to isolate the independent effects of cachexia. However, previous work showed that a similar model using female mice bearing C26 tumors exhibited relatively little body weight loss and cardiac atrophy after 21 days with tumors 20 , 50 , 51 . Despite decreased fractional shortening in vivo, myocytes from these animals had no change in contraction amplitude compared to controls, and inconsistency between studies in the time required to complete a contraction/relaxation cycle.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study revealed that dysregulated matrix metalloproteinases (MMPs) could contribute to detrimental molecular remodelling, resulting in cardiac abnormalities. A preclinical study conducted on 10-week-old CD2F1 female mice inoculated with C26 adenocarcinoma cells revealed that the administration of minocycline, an inhibitor of MMP, could improve cardiac function by restoring the contractility of cardiac myocytes and attenuating collagen I and III expression in the cardiac muscles [140]. Simvastatin (10 mg/kg/day once daily for 14 days), the inhibitor of the production of matrix metalloproteinase-9 and the drug of choice for dyslipidaemia, which is an important risk factor for cardiovascular disorders, was able to improve cardiac output (57.0 mL/min) in young Wister Han rats that had been injected with Yoshida AH-130 hepatoma cells compared to those who had been injected with a placebo (42.4 mL/min) and thus decreased the mortality rate (HR: 0.16, 95% CI: 0.04-0.76, p = 0.021) in the treated animals [141].…”
Section: Pharmacotherapymentioning
confidence: 99%